Cymbidium dianlan, nom. nov. for C. yunnanensis G.Q.Zhang & S.R.Lan (Orchidaceae) from China - He, Hai (Phytotaxa, 2019)
The epithet of recently published Cymbidium yunnanensis G.Q.Zhang & S.R.Lan in Zhang et al. (2019: 155) does not agree with the gender of the generic name. This is a correctable error based on Art. 23.5 of ICN (Turland et al. 2018) and it should be C. yunnanense G.Q.Zhang & S.R.Lan. However, it is a later homonym blocked by C. yunnanense Schlechter (1919: 74). To make the name of this new taxon applicable, the illegitimate name C. yunnanensis G.Q.Zhang & S.R.Lan is here replaced by C. dianlan H.He. The epithet dianlan is from the pinyin of two Chinese characters: dian means Yunnan and lan orchid, which take the same meaning of the suggested Chinese name of this new orchid by Zhang & Lan in Zhang et al. (2019). In Flora of China, Liu et al. (2009) has treated C. yunnanense Schltr. as a synonym of C. goeringii (H.G.Reichenbach 1845: 334) H.G.Reichenbach (1852: 547).